Grounded theory research on the factors that lead to doctor moral hazard - Wang, Yaohui; Dong, Jiankun; Wang, Xifeng; Liu, Quanlong; Li, Xinchun (Saúde e sociedade, 2021)
Abstract Moral hazard clearly exists among doctors, and it has a dramatic impact on doctor-patient relationships, medical costs and medical risks. This study explored the factors that lead to doctor moral hazard, as well as the interrelationships and internal regularity of these factors. This study takes doctor moral hazard as the research content and the inducing factors as the core theme, conducting grounded theory research on the causes of doctor moral hazard. Scientific understanding of doctor behavior would facilitate the prevention and control of doctor moral hazard behavior. This study used the principles and methodology of Glaser and Strauss’s grounded theory. Theoretical and snowball samplings were used to identify 24 subjects. Semi-structured in-depth interviews were conducted with each subject. Themes were identified through substantial (open) coding and theoretical coding. The factors that lead to doctor moral hazard were categorized into five dimensions, i.e. motivation, opportunity, self-rationalization, exposure and punishment. These five factors influence each other, forming the inducing mechanism of doctor moral hazard. This will provide useful theoretical support and method guidance for the follow-up prevention and control of moral hazard for doctors. Resumo O risco moral existe claramente entre os médicos e tem um impacto dramático nas relações médico-paciente, custos e riscos médicos. Este estudo explorou os fatores que levam ao risco moral por parte do médico, bem como as inter-relações e a regularidade interna desses fatores. Este estudo considera o risco moral do médico como o conteúdo da pesquisa e os fatores indutores como o tema central, conduzindo pesquisas de teoria fundamentada sobre as causas do risco moral do médico. A compreensão científica do comportamento do médico facilitaria a prevenção e o controle do comportamento de risco moral do médico. Este estudo usou os princípios e a metodologia da teoria fundamentada de Glaser e Strauss. Amostragens teóricas e em snowball foram utilizadas para identificar 24 sujeitos. Entrevistas semiestruturadas em profundidade foram realizadas com cada sujeito. Os temas foram identificados por meio de codificação substancial (aberta) e codificação teórica. Os fatores que levam ao risco moral do médico foram categorizados em cinco dimensões: motivação, oportunidade, autorracionalização, exposição e punição. Esses cinco fatores influenciam-se mutuamente, formando o mecanismo indutor do risco moral médico. Isso fornecerá suporte teórico útil e orientação metodológica para o acompanhamento da prevenção e controle de risco moral para os médicos.